Effects of Aging and Exercise on the Cardiorespiratory Fitness of Older Women - Kohler,Renan (2016)
Abstract Purpose: The present study analyzed the effects of chronological aging and the practice of regular exercise (PRE) on the cardiorespiratory fitness (CRF) of older women. Methods: A descriptive study of 78 participants was performed, with longitudinal design and an initial evaluation in 2005 and a second in 2011. The PRE defined groups as Inactive (I), Insufficiently-Active (IA), and Sufficiently-Active (SA). The six-minute walking test measured CRF. MANOVA with repeated-measures was used to verify the effect of time and the PRE groups on CRF (p<0.05). Results: The participants were classified as having a low socioeconomic level and being overweight. MANOVA demonstrated the effect of time (F1.74=30.134; p<0.05) and groups (F2.74=3.729; p<0.05), without interaction (F2.74=0.811; p>0.05). Post hoc analysis indicated that the effect of time was significant between all groups (I: t=3.786, p<0.05; IA: t=2.597, p<0.05; SA: t=3.191, p<0.05); and the group effect was significant only between the I and SA groups in the second evaluation (First evaluation: F2.76=1.712; p>0.05; Second Evaluation: F2.77=3.239; p<0.05, post hoc Tukey: group I vs AS =p<0.05). A smaller reduction in CRF was found in the SA group (8.0%), followed by the IA (10.3%) and I (14.3%) groups. Conclusion: The results of the present study indicated that elderly women who practice exercise regularly had a smaller reduction in CRF than those who were inactive. This suggests that the PRE at recommended levels for health purposes can attenuate the effect of aging on the CRF.